장애아동 가족을 위한 돌봄지원 개념화: 개념도 연구법을 활용하여 - 김유리; 최복천; Kim, Yu-Ri; Choi, Bogcheon (한국콘텐츠학회 논문지, 17(9), 2017)
Caregiving supports have been provided to decrease caregiving burdens of families of children with disabilities, but there are needs for improving caregiving services. The purpose of this study was to conceptualize content items and domains of caregiving supports from the perspectives of parents and service providers in order to help families of children with disabilities to decrease their caregiving burdens. This study used concept mapping that was useful for service-needs identification and program development. First, focus group interviews with two parent groups and one service provider group were conducted to generate a total of 31 items. Also, they sorted the items in terms of conceptual similarity and rated the items in terms of their needs. Next, the sorting data were analyzed using multidimensional scaling and cluster analysis and the rating data were calculated for mean. The results provided 31 content items in four domains: regular caregiving, activity-based caregiving, parent empowerment for caregving, and strengthening family relationships. All the domains were rated as important to decrease caregiving burdens. This study has practical implications for improving caregiving services and the related policies. 장애아동 부모 및 가족의 돌봄부담을 경감시키기 위한 돌봄지원이 제공되고 있지만 몇몇 한계점이 지적되면서 최근 들어 전반적인 개선이 요구되고 있다. 이에 본 연구는 장애아동 부모 및 서비스제공자의 관점에서 장애아동 가족의 돌봄부담 경감을 위해 필요한 돌봄지원의 내용 및 범위를 파악하고 개념화하는 것을 목적으로 하였다. 이를 위해 본 연구에서는 서비스 욕구조사 및 프로그램 개발에 유용한 개념도 연구법이 사용되었다. 개념도 연구법에 따라 먼저 장애아동 부모 두 집단과 사회복지사 한 집단을 대상으로 초점집단면담을 실행하여 총 31개의 돌봄지원 내용요소(진술문)를 도출하였으며, 연구 참여자들은 이 진술문들을 개념적 유사성에 따라 분류하고 상대적 필요도에 따라 평정하였다. 다음으로 분류자료들은 다차원 척도법과 군집 분석을 통해 분석되었으며, 평정자료들에 대해서는 평균과 표준편차를 산출하였다. 분석결과, 장애아동 돌봄지원 내용요소 31개는 4개의 범주로 개념화되었으며, 모든 범주의 필요도 점수는 높게 나타났다: 일상적 돌봄, 활동중심 돌봄, 부모 돌봄역량 강화, 가족관계 강화. 본 연구결과는 돌봄지원제도 개선 및 지원정책 개발에 유용한 기초자료를 제공하였다는 점에서 그 의의가 있다.